2019
DOI: 10.1186/s40663-019-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of harvesting intensities on structural diversity of forests in south-west Germany

Abstract: Background: To increase ecosystem resilience and biodiversity, the maintenance and improvement of structural and compositional diversity of forests has become an important goal in forest management for many forest owners and jurisdictions. At the same time, future harvesting intensity (HI) may increase to meet the demand for woody biomass by an increasing bioeconomy sector. Yet, the influence of HI on forest structural diversity is largely unknown. Here, we address this issue by analyzing the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Plant distribution information was obtained from the China Plants Database; spatial distribution data of mammals, amphibians, and reptiles were obtained from IUCN, and Colored Atlas of Chinese Amphibians and Their Distributions, supplemented with China’s Mammal Diversity and Geographical Distribution; bird spatial distribution data originated from Bird Life International; elevation and habitat vegetation types from China Plants Database, IUCN Red List, Bird Life International, and recent studies 23 . Elevation data came from the 90 m digital elevation model obtained in radar terrain detection mission of the NASA shuttle.…”
Section: Methodsmentioning
confidence: 99%
“…Plant distribution information was obtained from the China Plants Database; spatial distribution data of mammals, amphibians, and reptiles were obtained from IUCN, and Colored Atlas of Chinese Amphibians and Their Distributions, supplemented with China’s Mammal Diversity and Geographical Distribution; bird spatial distribution data originated from Bird Life International; elevation and habitat vegetation types from China Plants Database, IUCN Red List, Bird Life International, and recent studies 23 . Elevation data came from the 90 m digital elevation model obtained in radar terrain detection mission of the NASA shuttle.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the variable “harvesting intensity” ( HI ) as the ratio of the number of trees removed per year relative to the stand density of the three tree species obtained from the historical forest management plans. To assure that past management effects are correctly captured, we also repeated our analyses (see section below) with harvesting intensity defined as the percentage of wood volume removed from the stands (Storch and others 2019 ). Values of stand density (trees per ha), stand volume (m 3 per ha), harvested trees, and harvested volume from each stand are provided for each species and site in Appendix S4.…”
Section: Methodsmentioning
confidence: 99%
“…Annual precipitation and annual mean temperature range from 765 to 2141 mm and 5. 6-11.4°C, respectively (year 1991-2018Dietrich et al, 2019). The bedrock consists of gneiss and granite in the central, southern and western parts, sandstone in the northern part and limestone in the eastern part of the study region (State Office for Geology, Resources and Mining, Baden-Württemberg, Germany; maps.lgrb-bw.de; accessed 2023/2/16).…”
Section: Study Area and Study Designmentioning
confidence: 99%
“…Other studies addressed the role of specific deadwood characteristics, such as tree species, diameter, or stage of decay on species richness and community composition of deadwood-inhabiting taxa Krah et al, 2018;Lachat et al, 2013;Lassauce et al, 2011). To our knowledge, only few studies combined different aspects of deadwood to calculate measures for deadwood heterogeneity and related that to fungal diversity (Abrego & Salcedo, 2013;Heidrich et al, 2020;Pasanen et al, 2019;Penttilä et al, 2004;Storch, 2018). These studies found either no pattern or positive heterogeneity-diversity relationships.…”
Section: Introductionmentioning
confidence: 99%